Risk-adjusted long term social rates of discount for transportation infrastructure investment - Lars Hultkrantz; Niclas A. Krüger; Panagiotis Mantalos (Örebro University School of Business, 2012)
We modify a method recently suggested by Martin Weitzman (2012) for determining a risk-adjusted social discount rate (SDR) term structure consistent with both the (augmented) Ramsey rule and the consumption-based CAPM. Using this approach we estimate SDR for transportation infrastructure investments based on an analysis of correlations between transportation work, split on road and rail, and passenger travel and freight transport, and GDP in Sweden 1950-2011. We show that this can be estimated from two time-series following a random walk with drift, even if they are not co-integrated. Based on current estimates of the risk-free rate and the equity risk premium, we estimate the relevant SDR to be 5-6 percent, possibly somewhat lower for investment in railroads for passenger travel, and only slowly declining within the investment horizon. This is higher than the current rates used in, for instance, Sweden, Germany and the UK.
Keywords: D61; H43; L91; 330; Ramsey rule; CAPM; cost-benefit